Comparative Studies on Thermal Comfort Properties of Eri Silk, Wool/Eri Silk, Cotton, and Micro-denier Acrylic Double-layered Knitted Fabrics. Issue 15 (23rd November 2022) - Subburaayasaran, A.S.; Sampath Kumar, S. Kubera; Vasanth Kumar, D.; Ramachandran, T.; Prakash, C.; Vijayakumar, H.L.
ABSTRACT: In this study, 100% Eri Silk, 85:15% Wool/Eri silk, Cotton, and Micro-denier Acrylic yarns have been used to develop double-layered knitted fabrics. The thermal comfort properties such as air permeability, thermal resistance, thermal conductivity, and water vapor transmission have been evaluated. In this study, it is found that 100% eri silk double-layered knitted fabrics have better air permeability properties when compared with the other fabrics (85:15% Wool/Eri silk and 100% micro-denier acrylic fabrics) due to their thin and porous structure. As far as thermal conductivity is concerned, 100% Eri silk double-layered knitted fabrics have better thermal conductivity, whereas 85:15% wool/Eri silk double-layered knitted fabrics show poor thermal conductivity. In the case of thermal resistance, 85:15% wool/Eri silk double-layered knitted fabrics have maximum thermal resistance and 100% Eri silk shows poor thermal resistance when compared to other samples. A total of 100% Eri silk double-layered knitted fabrics have better water vapor transmission and 85:15% wool/Eri silk double-layered knitted fabrics have poor water vapor transmission when compared to other samples.